A Liquid-Chromatography High-Resolution Mass Spectrometry Method for Non-FDA Approved Benzodiazepines. Issue 4 (14th November 2018) - van Wijk, Xander M R; Yun, Cassandra; Hooshfar, Shirin; Arens, Ann M; Lung, Derrick; Wu, Alan H B; Lynch, Kara L
Abstract: Benzodiazepines (BZDs) are widely used for treatment of anxiety and insomnia, however, this class of drugs is also commonly abused. Many different BZDs and analogs have been produced that are not FDA-approved. We tested 15 of these with the ThermoFisher CEDIA® BZD-immunoassay. With the exception of ketazolam, all compounds showed significant reactivity, highlighting the need for mass spectrometry confirmation assays. We developed a liquid-chromatography high-resolution mass spectrometry method for the detection of these 15 non-FDA approved BZDs. The limit of detection for most compounds ranged from 1 to 50 ng/mL, with mostly positive matrix effects observed in urine and negative matrix effects in serum. In a clinical research case, clonazolam and etizolam were detected in serum at 10.2 and 281 ng/mL, with an apparent elimination half-life of 3.6 and 4.8 hours, respectively. Although we did not detect non-FDA approved BZDs in 211 urine samples that were previously determined to be BZD-positive by immunoassay, abuse of these drugs is on the rise and clinical and forensic toxicology laboratories should consider developing methods to detect them.